High‐Voltage Lithium‐Metal Batteries Enabled by Localized High‐Concentration Electrolytes - Chen, Shuru; Zheng, Jianming; Mei, Donghai; Han, Kee Sung; Engelhard, Mark H.; Zhao, Wengao; Xu, Wu; Liu, Jun; Zhang, Ji‐Guang (Advanced materials (Weinheim), 2018)
Rechargeable lithium‐metal batteries (LMBs) are regarded as the “holy grail” of energy‐storage systems, but the electrolytes that are highly stable with both a lithium‐metal anode and high‐voltage cathodes still remain a great challenge. Here a novel “localized high‐concentration electrolyte” (HCE; 1.2 m lithium bis(fluorosulfonyl)imide in a mixture of dimethyl carbonate/bis(2,2,2‐trifluoroethyl) ether (1:2 by mol)) is reported that enables dendrite‐free cycling of lithium‐metal anodes with high Coulombic efficiency (99.5%) and excellent capacity retention (>80% after 700 cycles) of Li||LiNi1/3Mn1/3Co1/3O2 batteries. Unlike the HCEs reported before, the electrolyte reported in this work exhibits low concentration, low cost, low viscosity, improved conductivity, and good wettability that make LMBs closer to practical applications. The fundamental concept of “localized HCEs” developed in this work can also be applied to other battery systems, sensors, supercapacitors, and other electrochemical systems. A novel “localized high‐concentration electrolyte,” which consists of 1.2 m lithium bis(fluorosulfonyl)imide in a mixture of dimethyl carbonate/bis(2,2,2‐trifluoroethyl) ether (1:2 by mol), enables dendrite‐free cycling of lithium‐metal anodes with high Coulombic efficiency of 99.3% and excellent capacity retention (>80% after 700 cycles) of Li||LiNi1/3Mn1/3Co1/3O2 batteries.